EFEKTIFITAS BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN MINAT BELAJAR MAHASANTRI XII IBNU KATSIR JEMBER - Armin, Ahmad Sidiq; Nasruliyah Hikmatul Maghfiroh; Ika Romika Mawaddati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study increases the interest in learning in male students at Ibnu Katsir Islamic Boarding School by using problem solving techniques. Problem solving is one technique that can solve problems faced realistically and can increase students' motivation and interest in learning. This technique is very relevant to the problems that will be studied in the field and applies 6 problem solving steps in research. This study uses quantitative research using the pre-experimental design method of the one group pretest-posttest type (initial test final test single group), in this study 4 stages will be carried out in the implementation of group guidance, namely the formation stage, transition, activities and termination. The results of the study indicate that this program is effective in increasing awareness, understanding, and motivation of students in recognizing their potential and career opportunities more clearly, helping them overcome confusion regarding their future careers